Effects of intraoperative Hartmann’s Solution with Stereofundin in renal transplant recipients / Wan Kamilah Hana Wan Nik Ahmad Mustafa - Wan Kamilah Hana, Wan Nik Ahmad Mustafa (2018)
Background Renal transplantation remains as the mainstay treatment for patients who suffer from end stage renal disease. Optimal graft perfusion and function after renal transplantation depends on adequate intravascular volume repletion. The ideal fluid for renal transplantation has not been defined. 0.9% saline has been used commonly in the past during perioperative period. Despite its frequent usage, 0.9% saline is associated with increased risk of hyperchloraemic metabolic acidosis, which also leads to delayed graft function in renal transplant recipients. Balanced crystalloids can substantially decrease the incidence of acidosis. This randomised controlled trial compares the effects of intraoperative Hartmann’s solution with stereofundin in renal transplant recipients, in terms of delayed graft function, measured by the need for dialysis at post operative day 7 or failure of serum creatinine to drop by 20% within 72 hours of renal transplant. Methods We recruited 11 patients undergoing elective living related renal transplant recipient from April 2018 to December 2018 at the University Malaya Medical Centre, Kuala Lumpur. Patients who refused to participate in this study were excluded. We recorded the serum creatinine at 72 hours post transplant and the need for dialysis at post operative day 7 as the primary outcome. We also compared the acid base status, serum potassium concentration, serum bicarbonate concentration at the end of surgery and post operative day 3, as well as any adverse events from the surgery. Results iv There is reduction plasma pH for both groups in immediate post operative period, but greater in Solution B group (0.071 ± 0.01, p<0.05). Solution B group also showed reduction in base excess (-4.6 ± 2.97, p<0.05), bicarbonate level (4.14 ± 1.16, p<0.05) and higher lactate level (2.26 ± 0.06, p<0.05) immediately post operation. Both groups showed reduction is serum creatinine (p<0.05) at POD 3, more pronounced with Solution B, despite the increment in lactate seen in this group at POD 3 (0.2 ± 0.06, p<0.05). None of the patients needed dialysis at POD 7, but the reduction in creatinine is higher in patients in Solution B group (665.4 ± 169, p<0.05). The potassium level in both groups were not statistically significant throughout the study. Conclusion There is no difference in occurrence of delayed graft function for both groups, but Solution B showed a lesser reduction in base excess and serum bicarbonate at POD 3. Solution B also showed significant increase in serum lactate at immediate post operative period and POD 3.